Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
Step-by-step explanation:
9x+[tex]\frac{1}{3}[/tex]=x-13
9x*3+1/3=x-13
27x+1/3=x-13
27x+1=3(x-13)
27x+1=3x-39
27x-3x=-39-1
24x=-40
x=-5/3
x=-5/3
Answer:
x = - [tex]\frac{5}{3}[/tex]
Step-by-step explanation:
Given
9x + [tex]\frac{1}{3}[/tex] = x - 13 ( multiply through by 3 to clear the fraction )
27x + 1 = 3x - 39 ( subtract 3x from both sides )
24x + 1 = - 39 ( subtract 1 from both sides )
24x = - 40 ( divide both sides by 24 )
x = [tex]\frac{-40}{24}[/tex] = - [tex]\frac{5}{3}[/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.